Helium cold atmospheric pressure plasma reduces erastin induced inflammation and ferroptosis in human gingival fibroblasts - Jung Sun Park; Young-Il Jeong; Byung-Hoon Kim (Scientific Reports)
Abstract Oral soft tissue damage can lead to hard tissue damage in the oral cavity, such as periodontal lesions, periapical disorders, cysts, and oral tumors. Cold plasma is known to alleviate inflammation and oxidative stress and promote tissue regeneration, yet the effects of helium plasma on human gingival cells remain poorly understood. In this study, we examined whether helium (He) cold atmospheric pressure plasma (CAP) can induce anti-inflammatory and anti-ferroptotic effects in oral soft tissues by ionizing He gas. Erastin treatment followed by He CAP exposure in human gingival fibroblast-1 (HGF-1) cells reduced the mRNA expression of inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2), interleukin-1β (IL-1β), tumor necrosis factor-α (TNFα), and interleukin-6 (IL-6), which are linked to inflammatory responses. Additionally, He CAP exposure decreased nuclear receptor coactivator 4 (NCOA4) expression and increased glutathione peroxidase 4 (GPX4) expression. Furthermore, mitochondrial membrane potential was restored by increased voltage-dependent anion channel 1 (VDAC1) expression, and reactive oxygen species (ROS) levels in mitochondria and cytoplasm were reduced. These results suggest that He CAP exposure may be associated with modulation of mitochondrial ROS production and reduction of inflammation and ferroptosis, but whether mitochondrial repair contributes to these effects requires further investigation.